The Feasibility of Targeted Magnetic Iron Oxide Nanoagent for Noninvasive IgA Nephropathy Diagnosis - Wu, Yaoyao; Huang, Qiang; Wang, Junli; Dai, Yuhua; Xiao, Ming; Li, Yangyang; Zhang, Hongbo; Xiao, Wenbo (Frontiers in Bioengineering and Biotechnology, 2021)
IgA nephropathy is the most common glomerular disease in the world and has become a serious threat to human health. Accurate and non-invasive molecular imaging to detect and recognize the IgA nephropathy is critical for the subsequent timely treatment; otherwise, it may progress to end-stage renal disease and lead to glomerular dysfunction. In this study, we have developed a sensitive, specific, and biocompatible integrin αvβ3-targeted superparamagnetic Fe3O4 nanoparticles (NPs) for the noninvasive magnetic resonance imaging (MRI) of integrin αvβ3, which is overexpressed in glomerular mesangial region of IgA nephropathy. The rat model of IgA nephropathy was successfully established and verified by biochemical tests and histological staining. Meanwhile, the clinical 18F-AlF-NOTA-PRGD2 probe molecule was utilized to visualize and further confirmed the IgA nephropathy in vivo via positron emission computed tomography. Subsequently, the Fe3O4 NPs were conjugated with arginine–glycine–aspartic acid (RGD) molecules (Fe3O4-RGD), and their integrin αvβ3-targeted T2-weighted imaging (T2WI) potential has been carefully evaluated. The Fe3O4-RGD demonstrated great relaxation in vivo. The T2WI signal of renal layers in the targeted group at 3 h after intravenous injection of Fe3O4-RGD was distinctly lower than baseline, indicating MRI signal decreased in the established IgA nephropathy rat model. Moreover, the TEM characterization and Prussian blue staining confirmed that the Fe3O4-RGD was located at the region of glomerulus and tubular interstitium. Moreover, no obvious signal decreased was detected in the untargeted Fe3O4 treated and normal groups. Collectively, our results establish the possibility of Fe3O4-RGD serving as a feasible MRI agent for the noninvasive diagnosis of IgA nephropathy.